2021
DOI: 10.1099/mgen.0.000667
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and genomic characterization of tigecycline-resistant tet(X4)-positive Escherichia coli of swine farm origin

Abstract: The emergence of plasmid-mediated tigecycline-resistant strains is posing a serious threat to food safety and human health, which has attracted worldwide attention. The tigecycline resistance gene tet(X4) has been found in diverse sources, but the distribution of tet(X4) and its genetic background in the animal farming environment is not fully understood. Thirty-two tet(X)-positive Escherichia coli strains isolated from 159… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 61 publications
2
29
1
Order By: Relevance
“…Pigs have been found to be important vehicles of tet (X4)-producing E. coli isolates, which is consistent with the results from previous studies [ 4 , 5 , 8 , 16 ]. Furthermore, the pig tet (X4)-producing E. coli isolates from Shaanxi differed by only 119 SNPs from the human isolates in a previous study from China [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Pigs have been found to be important vehicles of tet (X4)-producing E. coli isolates, which is consistent with the results from previous studies [ 4 , 5 , 8 , 16 ]. Furthermore, the pig tet (X4)-producing E. coli isolates from Shaanxi differed by only 119 SNPs from the human isolates in a previous study from China [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…Currently, tet (X4)-producing E. coli isolates have been disseminated in meat products such as pork and chicken, food animals, animal feces, and farm soil [ 3 , 4 , 5 , 6 , 7 ]. In a previous study, tet (X4)-producing E. coli isolates in pigs and chickens accounted for 1.3% and 0.8%, respectively, which was disseminated in five provinces in southern and eastern China including Guangdong, Fujian, Jiangsu, Jiangxi, and Guangxi [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…MW423609) from ST761 E. coli isolate SH19PTE6 collected from the same pig farm in 2019 ( Wang et al, 2021 ), and also showed high identity (> 99.7%) to multiple tet (X4)-carrying IncFIA18/IncFIB(K)/IncX1 plasmids from ST761 E. coli strains in China, such as pNT1W22-tetX4 (pig, CP075470), pRF108-2_97k_tetX (pig, MT219820), pSTB20-1T (pig, CP050174), p54-tetX (cow, CP041286), pYPE12-101k-tetX4 (pork, CP041443), and pYPE3-92k-tetX4 (pork, CP041453) ( Figure 2 ). Similar IncFIA18/IncFIB(K)/IncX1 plasmids harboring tet (X4) were also present among other E. coli lineages obtained from a pig farm in Jiangsu province, China ( Li Y. et al, 2021 ), e.g., pNT1N31-tetX4 (ST716, CP075481), pNT1F25-tetX4 (ST1421, CP075471), pNT1F31-tetX4 (ST206, CP045188), pNT1N25-tetX4 (ST641, CP075485), and pNT1F34-tetX (ST10115, CP075486) ( Figure 2 ), highlighting the importance role of horizontal transfer of plasmids in the tet (X4) dissemination between different bacteria.…”
Section: Resultsmentioning
confidence: 72%
“…Thus far, tet (X) and its variants [ tet (X1)∼ tet (X47)] have been identified in Gram-negative pathogens and encode flavin-dependent monooxygenase that modify tigecycline ( Aminov, 2021 ; Li R. et al, 2021 ; Umar et al, 2021 ; Zhang et al, 2021 ). Among them, the mobile tet (X4) gene has been increasingly identified in E. coli from various sources including food-producing animals, wild birds, food products, humans, and the environment, mainly in China ( He et al, 2019 ; Fang et al, 2020 ; Li et al, 2020 ; Li Y. et al, 2021 ; Dong et al, 2022 ; Liu et al, 2022 ). It has sporadically reported in countries outside of China, e.g., Singapore, Pakistan, Vietnam, United Kingdom, and Norway ( Ding et al, 2020 ; Marathe et al, 2021 ; Mohsin et al, 2021 ; Dao et al, 2022 ; Martelli et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation